Communication Patterns Of The Indonesian National Police In Confronting Radical Group Proganda On Social Media During The Covid-19 Pandemic - Yasmi Nur Hajizah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research explores the communication patterns employed by the Indonesian National Police (POLRI) in addressing propaganda from radical groups on social media during the Covid-19 pandemic. Utilizing a qualitative approach, the study analyzes POLRI's communication content on social media platforms and investigates the communication strategies implemented to counter radical group propaganda. The findings highlight POLRI's active efforts in utilizing social media as a means to convey real-time information regarding their actions, with an emphasis on national values and the promotion of diversity. An analysis of the social media content of radical groups is also conducted to understand their communication strategies and online behavioral patterns. The research reveals the complex dynamics in the interaction between POLRI and radical groups in the virtual sphere, showcasing challenges and both positive and negative responses from the public to police efforts. Practical implications of the research include recommendations to enhance the capacity of police personnel in managing social media, intensifying collaboration with social media platforms, and increasing transparency in disseminating information to the public as measures to enhance the effectiveness of police communication in tackling propagandistic challenges from radical groups during this pandemic era.